Halal Label and BPOM Label on the Purchase Intention of Cosmetics in West Aceh Reviewed in the Perspective of Islamic Economics - Pramadia, Rinda; Adnan, Muhammad; Syahputra, Hendra (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2024)
Halal label and BPOM label are legalities that must be present in a cosmetic product. With the halal label and BPOM label, it can increase consumer confidence and buying interest. This study aims to analyse the effect of halal labels and BPOM labels on buying interest in cosmetics in West Aceh Regency from an Islamic economic perspective. This research uses quantitative methods with a survey approach. Primary data was obtained by distributing questionnaires to 110 respondents with purposive sampling technique, the data analysis method used was multiple linear regression with the help of the SPSS 26 application program. The results showed that partially the halal label variable had no significant effect on buying interest. While the BPOM label variable affects buying interest. Simultaneously the halal label variable and the BPOM label variable have a positive and significant effect on buying interest. The coefficient of determination R Square of 0.269 or 26.9% means that the contribution of variable X to variable Y is 26.9%, while the remaining 73.1% is influenced by other factors outside this study. The correlation coefficient (R) value of 0.519 or 51.9% means that variable X has a sufficient influence on variable Y.